Anisotropy of acoustic emission and Portevin– Le Châtelier phenomena in polycrystalline aluminium alloys subjected to tensile tests - Pawełek, A; Kuśnierz, J.; Jasieński, Z.; Ranachowski, Zbigniew (Archives of Acoustics, 2006)
In the present work the acoustic emission (AE) method has been used in the plastic instabilityinvestigations related to the Portevin–Le Châtelier phenomenon (PL effect, nonhomogeneousstrain, jerky flow) occurring in polycrystalline aluminium alloys subjected totensile tests at ambient temperature. There have been observed very essential correlationsbetween AE and PL phenomena and a strong anisotropy of both these effects in samplescut at various angles with respect to the initial rolling direction has been found. The resultsof AE measurements were obtained using a new AE analyser and, for a few samples, theyhave been compared with those obtained applying an analyser of older generation, used tillnow. Moreover, the new software allowed additionally to carry out the analysis of single AEevents, which, in turn, created better possibility to determine the relations between the nonhomogeneousstrain mechanisms of the PL type and the mechanisms of AE events generation.The results are discussed also in the context of the existing models of the PL effect and thetheoretical concepts of AE sources.